Effect of restricted feeding on productivity of Mojosari X Alabio cross-bred layer ducks (MA): Growing phase to point at lay - P.P Ketaren; L.H Prasetyo (Indonesian Center for Animal Research and Development (ICARD), 2007)
Feed efficiency of layer ducks is low since feed consumption is considerably higher than egg production. The experiment has been conducted to evaluate performances and age at first laying of MA crossbred duck from 1-20 weeks old on restricted feeding. Three experimental diets tested were: (1) 70% ad libitum = 70% A, (2) 85% ad libitum = 85% A and (3) 100% ad libitum = 100% A. Feed consumption, live weight gain (PBB), feed conversion ratio (FCR), mortality rate and age at first laying were recorded. Live weight gain of ducks on 70 and 85%A were significantly (P<0.05) lower than 100% A for both at 12 weeks old. Live weight gain of duck at 16 weeks old fed 85% A was similar to the ducks fed 100% A. On the other hand, FCR of duck at 16 weeks old on 70 and 85% A were significantly (P<0.05) better than ducks fed 100% A diet. Age at first laying was delayed 9 days on duck fed 85% A and 21 days on duck fed 70% A diet. However, average weight of first laid egg was not affected by the treatments. Mortality increased on duck fed 70% A. This study indicated that feeding MA duck at rate of 85% of ad libitum was sufficient to support normal growth and reproductive development. Key Words: MA Crossbred Duck, Restricted Feeding, Growth, Age at First Laying